P125 Stop smoking as treatment for COPD: quit-interventions of higher intensity and duration are required. (2nd December 2011) - Browne, J; Aslam, N; Jones, E; Flint, B; Dzingai, J; Fabris, G; Billett, J; Restrick, L; Stern, M
Abstract : Introduction and Objectives: Smoking cessation is one of the most cost-effective interventions for COPD (£2092/QALY; Hoogendoorn et al 2010). Smokers with COPD should therefore be offered intensive quit-smoking support as treatment for their disease. The aim of this study was to assess the efficacy of standard quit-smoking interventions (NICE, 2008) for COPD-smokers, to determine levels of support required to improve quit rates. Methods: Current smokers with confirmed COPD were referred from within an inner-city general hospital (inpatients/outpatients) to a dedicated quit-smoking specialist (QSS) or from the community COPD-multidisciplinary team to an integrated QSS, who undertook domiciliary visits for housebound smokers. Both QSS had additional counselling skills. Demographics, disease severity (FEV1 ), smoking history, duration of quit-smoking treatment, pharmacotherapy and quits (4 week) were prospectively recorded over 11 months (September 2010–July 2011). Results: 106 patients with moderate COPD M:F 39:67, mean±SD age 66.4±10.4 y range 49–85; FEV1 1.2±0.6l, n=76) were referred: 63 (69%) hospital patients (HP), 43 (41%) from the community (CP). Compared to the HP who had mean±SD FEV1 1.4±0.5 l, and smoked 23.5±11.4 cigarettes/day on referral, CP had significantly (p=0.03) worse lung function (FEV1 1.2±0.5 l) but smoked fewer (p=0.002) cigarettes/day (9.8±8/day). 25/106 (24%) patients quit, but quits were significantly lower (p<0.05) in the CP (20%) compared to the HP (30%). 45/106 (42%) were not able to set a quit-date, 5/106 (5%) set multiple quit-dates. 56/106 (53%) used nicotine replacement therapy (NRT), >2 products in 48/56. 18/106 (17%) used varenicline, seven sequentially following NRT. Duration of pharmacotherapy for quitters was 6.1±4.5 months (mean±SD, range 1–16). 38/106 (36%) were discharged after lost to follow-up. Conclusions: These data demonstrate that 1-in-4 smokers with COPD are able to quit using evidence based tobacco addiction treatment. However, quit rates for these smokers are much lower than the Department of Health (DH) expectation of >35%, despite intensive interventions by skilled QSS, domiciliary visits to housebound patients, and pharmacotherapy extended beyond the standard 8–12 weeks. Novel approaches, including addressing psychosocial issues, motivational quit-date setting, review of the DH 4-week quit-target and sufficient funding for extended NRT/Varenicline prescribing, may be required to achieve effective smoking cessation in this patient group.